DISCLOSURE OF CORONAVIRUS DISEASE-19 (COVID-19) PATIENT DATA: ETHICAL AND LEGAL PERSPECTIVES IN INDONESIA - Budiyanti, Rani Tiyas; Herlambang, Penggalih Mahardika (Bagian Dasar-Dasar Ilmu Hukum & Hukum dan Masyarakat Fakultas Hukum Universitas Diponegoro, 2021)
The contact tracing policy strategy implemented during the COVID-19 pandemic requires data on COVID-19 patients to be accessible to the public so that people who have been in contact with the positive patient can do self-isolate. However, this is contrary to medical secrets and the confidentiality of COVID-19 patient data as a form of private law. This research is normative research with a statutory approach (statue approach) and conceptual (conceptual approach). Based on ethical and legal aspects, the confidentiality of COVID-19 patient data must be maintained. This data can be disclosed with the patient consent or disclosed to the Health Office to conduct epidemiological investigations. Suppose the contact investigation involves several parties: the neighborhood unit, the village head, Village Community Empowerment Service, police, and other parties. In that case, further regulation is needed to ensure the commitment of these parties in maintaining COVID-19 patient data. Disseminating patient data openly or publicly can make harm to the patient, especially in the not good environment with risk of stigmatization. There is also a need for harmony between existing regulations and the programs or policies implemented by the government.